Effects of tocilizumab on mortality in hospitalized patients with COVID-19: a multicentre cohort study. (February 2021) - Martínez-Sanz, Javier; Muriel, Alfonso; Ron, Raquel; Herrera, Sabina; Pérez-Molina, José A.; Moreno, Santiago; Serrano-Villar, Sergio
Abstract: Objectives: Tocilizumab has been proposed as a candidate therapy for patients with severe coronavirus disease 2019 (COVID-19), especially among those with higher systemic inflammation. We investigated the association between receipt of tocilizumab and mortality in a large cohort of hospitalized patients. Methods: In this cohort study of patients hospitalized with COVID-19 in Spain, the primary outcome was time to death and the secondary outcome time to intensive care unit (ICU) admission or death. We used inverse probability weighting to fit marginal structural models adjusted for time-varying covariates to determine the causal relationship between receipt of tocilizumab and outcome. Results: Data from 1229 patients were analysed, with 261 patients (61 deaths) in the tocilizumab group and 969 patients (120 deaths) in the control group. In the adjusted marginal structural models, a significant interaction between receipt of tocilizumab and high C-reactive protein (CRP) levels was detected. Tocilizumab was associated with decreased risk of death (adjusted hazard ratio 0.34, 95% confidence interval 0.16–0.72, p 0.005) and ICU admission or death (adjusted hazard ratio 0.39, 95% confidence interval 0.19–0.80, p 0.011) among patients with baseline CRP >150 mg/L but not among those with CRP ≤150 mg/L. Exploratory subgroup analyses yielded point estimates that were consistent with these findings. Conclusions: In this large observational study, tocilizumab was associated with a lower risk of death or ICU admission or death in patients with higher CRP levels. While the results of ongoing clinical trials of tocilizumab in patients with COVID-19 will be important to establish its safety and efficacy, our findings have implications for the design of future clinical trials.